Survival of the fittest: mortality and longevity in male Australian elite rugby union players - Lystad, R. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Previous studies have reported that elite athletes from a wide range of sports live longer than the general population. The survival benefit of participation in elite sports is generally attributed to decreased risk of mortality caused by cardiovascular disease and cancer. However, there may be considerable variation in athlete survival and longevity between and within sports. For instance, in contact sports with high risk of repetitive head trauma there are concerns that the survival benefit may be offset by increased risk of mortality from other causes such as neurodegenerative disease. This study quantified survival and longevity among male Australian elite rugby union players compared to sex- and age-matched referents from the general population. METHODS: This retrospective cohort study included male rugby union players who had their Australian national team debut from 1 January 1921 to 31 December 2023. The cohort was identified by cross-referencing rugby statistics from open online sources (i.e. classicwallabies.com.au, ESPNscrum.com, and www.wikipedia.com). Cohort data included athlete name, date of birth, date of national team debut, player position, and date of death. Data on sexand age-specific all-cause mortality in the Australian general population were obtained from life tables available from the Human Mortality Database (www. mortality. org). Survival time was calculated from the date of national team debut until the date of death or end of the follow-up period (i.e. 31 December 2023). To avoid issues with high variability due to data sparsity at very old ages, athletes were censored at age 90 years. Survival analysis was performed using the Kaplan-Meier estimator and longevity gains or losses were quantified using the life years difference method and presented with 95% confidence intervals. Differences between forwards and backs were examined using a log-rank type test comparing net survival curves. RESULTS: The cohort comprised 801 athletes with a median age at national team debut of 23.3 (IQR 21.8 to 25.6) years. By the end of the study follow-up period, 310 (38.7%) athletes were deceased, with a median age at death of 74.6 (IQR 64.0 to 82.1) years. Maximum net survival was observed at 47.6 years post-debut, at which point the average life years gained was 0.33 (-0.29 to 0.96) years. After this peak, there was a steady decline in net survival, with minimum net survival observed at 70.4 years post-debut, at which point the average life years lost was 0.82 (-0.39 to 2.03) years. There was no significant difference in net survival between backs and forwards (p=0.597). CONCLUSION: Unlike elite athletes in many other sports, there was no observable survival benefit among male Australian elite rugby union players compared to the general population. Further research examining disease-specific mortality is needed to elucidate the underlying reasons for the absence of longevity gains among male Australian elite rugby players.